Delivering more with less: Subnational service provision in low capacity states - Kyle, Jordan; Resnick, Danielle (Springer, 2019)
In developing countries, low state capacity frequently is blamed for poor and uneven service delivery. Yet, since state capacity manifests unevenly across space and sectors, identifying which elements of capacity are more likely to enhance service delivery is not straightforward. We examine how subnational variation in capacity affects access to agricultural extension in rural Nepal. We explore six dimensions of state capacity using original household survey data and interviews with local bureaucrats. We find that local knowledge and motivation of bureaucrats play a significant role in shaping service access. By contrast, traditional capacity indicators—including resources, professionalization, and autonomy—matter surprisingly little. These findings suggest that bureaucrats working with fewer but more motivated staff who spend more time in a district are more likely to facilitate citizens’ access to agricultural extension. Placebo tests add confidence that relationships are not driven by unobservables. Scholarship on state capacity traditionally has been unable to measure capacity disaggregated by geography and sector, and, as a result, has struggled to link empirically different elements of capacity with service delivery. This paper begins to address this gap and in doing so, offers broader implications for the dynamics of rural development.